Pharmacological Resistance of Stress Enhanced Fear Learning in an Animal Model of Post-Traumatic Stress Disorder - Long, Virginia; Fujioka, Wendy; Amir, Dorsa; Fanselow, Michael (IntechOpen, 2011)
None